Seorang Wanita dengan Cor Pulmonale Terkait Silikosis : [Cor Pulmonale in a Woman with Silicosis: A Case Report] - Abdul Rahman Bahmid; Helmia Hasan (Jurnal Respirasi, 2019)
Background: Silicosis is a pulmonary fibrosis disease caused by inhalation of silica crystals (silicon dioxide). Silica is a material that can be found everywhere which is the main component of the earth's crust. There are three main forms of silica crystals that cause lung injury, namely quartz, cristobalite, and tridymite. Quartz is the most commonly found silica in most rocks, including granite and sandstone. Case:A housewife aged 47 years experienced shortness since 1 month disappeared, and weighed the last 1 week. Shortness especially during activity. Cough once in a while, with white phlegm. Swelling in both legs since more than 1 month. There is no history of asthma, pulmonary TB, and DM. The patient is a housewife. About 15 years ago the patient had worked in a rubber factory for 2 years. Conclusion: Silicosis is always associated with pulmonary TB, because silicosis patients have a high risk of developing pulmonary TB. To detect the presence of pulmonary TB in these patients we have carried out smear smear and geneXpert tests of sputum specimens with negative results. Examination of M.tb from culture of induced sputum material has been carried out but the results have not been obtained.